Routines in Web Journalism: Multitasking and Time Pressure on Web Journalists - Fernandes, Sarita González; Jorge, Thaïs de Mendonça (Brazilian journalism research, 2017)
The Internet has brought changes to journalism and the routines of news producers. Over time, professionals in online journalism have had to take on more tasks within the same news making process; one which is replete with speed. This article analyzes how multitasking enhances time pressure in the production routines of web journalism. The research used for the analysis was a collection of in-depth interviews conducted with web journalists from two websites in Brasília. The results from these interviews show that online producers tend to compare themselves with other media professionals. They also believe that they multitask more than other journalists do. Multitasking is seen as one of the aggravating factors leading to time pressure in production routines. It also raises other questions about web journalism. A internet implica transformações no jornalismo e nas rotinas dos produtores da notícia. Ao longo do tempo, o exercício do jornalismo em rede agregou outras tarefas a serem executadas pelos profissionais em um mesmo processo de produção da notícia, permeado pela rapidez. O artigo objetiva analisar como as multitarefas potencializam a pressão do tempo nas rotinas produtivas do webjornalismo. Para a análise, foram aplicadas como técnica de pesquisa entrevistas em profundidade com webjornalistas de dois sites de notícias de Brasília. Os resultados apontam que os webjornalistas tendem a se comparar com profissionais de outras mídias e se consideram jornalistas mais multitarefas do que os demais. As multitarefas são interpretadas como um dos agravantes da pressão do tempo nas rotinas produtivas, além de levantarem outros questionamentos sobre o webjornalismo. La internet implica transformaciones en el periodismo y en las rutinas de los productores de noticias. Con el tiempo, el ejercicio del periodismo en red añadió otras tareas para los profesionales en un mismo proceso de producción de noticias, impregnado por la velocidad. Este trabajo tiene como objetivo evaluar como las multitareas potencian la presión del tiempo en las rutinas productivas en ciberperiodismo. Para el análisis, se aplicaron como una técnica de investigación entrevistas en profundidad con periodistas de internet de dos sitios web de noticias de Brasilia. Los resultados muestran que los ciberperiodistas tienden a compararse con profesionales de otros medios y consideran que son más multitareas que otros periodistas. Las multitareas son interpretadas como un agravante de la presión del tiempo en las rutinas productivas y que causan otras cuestiones sobre el ciberperiodismo.